2008
DOI: 10.1007/s10265-008-0173-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth temperature and winter duration on leaf phenology of a spring ephemeral (Gagea lutea) and a summergreen forb (Maianthemum dilatatum)

Abstract: Effects of growth temperature and winter duration on leaf longevity were compared between a spring ephemeral, Gagea lutea, and a forest summergreen forb, Maianthemum dilatatum. The plants were grown at day/night temperatures of 25/20 degrees C and 15/10 degrees C after a chilling treatment for variable periods at 2 degrees C. The temperature regime of 25/20 degrees C was much higher than the mean air temperatures for both species in their native habitats. Warm temperature of 25/20 degrees C and/or long chillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Previous studies demonstrated that vegetative growth of spring ephemerals was terminated by the increase in soil temperature because warm temperature activated the metabolic process of aging (Badri et al 2007;Yoshie 2008). These studies suggest that growing season length of spring ephemerals may be determined by temperature regime but not by light environment.…”
Section: Is Carbon Fixation Sink-limited?mentioning
confidence: 76%
“…Previous studies demonstrated that vegetative growth of spring ephemerals was terminated by the increase in soil temperature because warm temperature activated the metabolic process of aging (Badri et al 2007;Yoshie 2008). These studies suggest that growing season length of spring ephemerals may be determined by temperature regime but not by light environment.…”
Section: Is Carbon Fixation Sink-limited?mentioning
confidence: 76%
“…These two species have perennial shoot axes (Yoshie 2008a). In contrast, the growth period of Maianthemum dilatatum (a species distributed in Murodo-daira) and Gagea lutea in the cool temperate region, both of which have annual shoot axes with a predetermined number of leaves, was shorter at cultivation temperatures of 25/20°C than 15/10°C (Yoshie 2008b). These results suggest that warm air temperatures lengthen the growth period of herbs with perennial shoot axes and, conversely, shorten the growth period of herbs with annual shoot axes and a predetermined number of leaves.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, previous studies indicated that a warm temperature significantly shortened the leaf expansion period of temperate herbs that have a determinate growth habit. The expansion period was shorter at 20°C (approximately 11 days) than at 10°C (18 days) in Erythronium japonicum, a spring ephemeral (Yoshie and Fukuda 1994), and was also shorter at 25/20°C (17 days) than at 15/10°C (33 days) in Gagea lutea, a spring ephemeral and at 25/20°C (9 days) than at 15/10°C (12 days) in Maianthemum dilatatum, a summergreen geophyte (Yoshie 2008a). These results suggest that the increased expansion period of plants due to warm temperatures is a trait common to herbs with an indeterminate growth habit.…”
Section: Discussionmentioning
confidence: 89%
“…Increased temperature reduces the expansion period of individual leaves (e.g. Dennet and Auld 1980;Rawson and Dunstone 1986), thus the leaf expansion period of plants with a determinate growth habit is shortened with increasing temperatures (Yoshie and Fukuda 1994;Yoshie 2008a). Because plant growth and development are strong functions of temperature, warmer temperatures increase the rate of ontogenetic development and result in a substantial shortening of the shoot expansion period (the time to flowering) in determinate annual species (Morison and Lawlor 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation